Nuevos postulados básicos en la contabilidad mundial (2015)
This research was especially prepared in the month of June 2013, for the XVIII International Congress of Accounting, Management and Information Technology to be held in Mexico City DF on the 2ndand 3rd of October of 2013. The overall objective is to examine the implementation of the nine basic postulates in light of the traditional accounting principles generally accepted. The research developed is analytical-explanatory documentary and a bibliographic synthesis of books, international accounting research journals, abstracts and Web pages. The main finding shows that there are high quality standards geared to the investor, prioritizing financial rather than economic concerns, from the consensus reached by different theoretical approaches developed in recent decades, validated by businesspractice and whose aim is to reflect the economic essence of operations, and to present a fair view of the financial position of the company. IFRS are issued by the International Accounting Standards Board (IASB), (former International Accounting Standards Committee).